Synthesis and Anticonvulsant Activity of (R)- and (S)-3-(Carbobenzyloxy-amino-1-glutarimidooxy)esters - Lee, Do-Hun (Asian Journal of Chemistry, 2013)
A series of (R)- and (S)-3-carbobenzyloxy-amino-1-glutarimidooxy-esters (5a-e) ((R)-and (S)-methyl-1-(3-carbobenzyloxy-amino-glutarimidooxy)acetate (5a), (R)-and (S)-ethyl-1-(3-carbobenzyloxy-amino-glutarimidooxy)acetate (5b), (R)- and (S)-ethyl-1-(3-carbo-benzyloxyamino-glutarimidooxy)propionate (5c), (R)- and (S)-methyl-2-(3-carbobenzyloxy-amino-glutarimidooxy)butyrate (5d), (R)- and (S)-ethyl-2-(3-carbobenzyloxy-amino-glutarimidooxy) butyrate (5e) were synthesized and investigated their anticonvulsant activities.